High-entropy materials for energy-related applications - Fu, Maosen; Ma, Xiao; Zhao, Kangning; Li, Xiao; Su, Dong (iScience, 2021)
High-entropy materials (HEMs), including high-entropy alloys (HEAs), high-entropy oxides (HEOs), and other high-entropy compounds, have gained significant interests over the past years. These materials have unique structures with the coexistence of antisite disordering and crystal periodicity, which were originally investigated as structural materials. Recently, they have emerged for energy-related applications, such as catalysis, energy storage, etc. In this work, we review the research progress of energy-related applications of HEMs. After an introduction on the background, theory, and syntheses of HEMs, we survey their applications including electrocatalysis, batteries, and others, aiming to retrieve the correlations between their structures and performances. In the end, we discussed the challenges and future directions for developing HEMs. [Display omitted] Physics; Materials Science; Energy Materials